Borane Adducts of Aromatic Phosphorus Heterocycles: Synthesis, Crystallographic Characterization and Reactivity of a Phosphinine‐B(C6F5)3 Lewis Pair. Issue 7 (20th January 2022) - Lin, Jinxiong; Wossidlo., Friedrich; Coles, Nathan T.; Weber, Manuela; Steinhauer, Simon; Böttcher, Tobias; Müller, Christian
Abstract: A phosphinine‐borane adduct of a Me3 Si‐functionalized phosphinine and the Lewis acid B(C6 F5 )3 has been synthesized and characterized crystallographically for the first time. The reaction strongly depends on the nature of the substituents in the α‐position of the phosphorus heterocycle. In contrast, the reaction of B2 H6 with various substituted phosphinines leads to an equilibrium between the starting materials and the phosphinine–borane adducts that is determined by the Lewis basicity of the phosphinine. The novel phosphinine borane adduct (6 ‐B(C6 F5 )3 ) shows rapid and facile insertion and [4+2] cycloaddition reactivity towards phenylacetylene. A hitherto unknown dihydro‐1‐phosphabarrelene is formed with styrene. The reaction with an ester provides a new, facile and selective route to 1‐ R ‐phosphininium salts. These salts then undergo a [4+2] cycloaddition in the presence of Me3 Si−C≡CH and styrene to cleanly form unprecedented derivatives of 1‐ R ‐phosphabarrelenium salts. Abstract : Roll out the barrelene : The synthesis and crystallographic characterization of a phosphinine–borane adduct has been achieved for the first time. The novel Lewis adduct shows rapid insertion and [4+2] cycloaddition reactivity towards phenylacetylene, whereas a hitherto unknown dihydro‐1‐phosphabarrelene is formed with styrene. Reaction with an ester provides a new, facile and selective route to 1‐ R ‐phosphininium salts. These subsequently undergo a [4+2] cycloaddition in the presence of alkenes and alkynes to cleanly form unprecedented derivatives of 1‐ R ‐phosphabarrelenium salts.